MULTIMODALITY IN THE ENGLISH TEXTBOOK IMAGES : GENDER REPRESENTATION ANALYSIS - Hidayah, Fithrah Nurul; Purnomo, Maslathif Dwi; Daulay, Sholihatul Hamidah (Getsempena English Education Journal, 2025)
Gender representation in educational materials plays a crucial role in shaping students’ perceptions of societal roles. Previous studies have predominantly examined gender representation through written text, often overlooking the visual dimension, particularly in English textbooks. This study investigates gender representation through images in a tenth-grade English textbook using a multimodal discourse analysis, specifically focusing on representational aspects. A total of 131 images were examined, but only three met the criteria for analysis—each featuring both male and female human participants. These images were analyzed based on the roles, actions, and contexts in which each gender was portrayed. The findings indicate a balanced and non-stereotypical representation. In the first image, a male and a female student appear as academic equals without hierarchical cues. The second image features two women and one man in a professional environment, where one woman assumes a leadership position. The third image depicts a mixed-gender social setting with equal participation and non-hierarchical interaction. These portrayals challenge conventional gender stereotypes and suggest a shift toward more equitable and inclusive gender representation. The results underline the importance of visual analysis in identifying and promoting gender balance in learning materials. It is recommended that educational content developers incorporate more images that reflect gender equality across various domains to support a more inclusive learning environment.